Improving Constructive Alignment and Deep Learning: Integrating Multiple Learning Activities - Vestergaard, Marianne (Improving University Science Teaching and Learning, 2023)
How can I change the format of a traditionally lecture-based and problemsolving Astronomy Bachelor course to create an inspiring deep-learning environment that both satisfies the intended learning outcomes (ILOs), provides student engaging teaching/learning activities (TLAs), and contributes to a constructive alignment between TLAs and course evaluations (exams, project reports, etc) and between this course and the Bachelor education in physics with specialization in astronomy? I made several changes to this course in 2010 with the purpose of improving student active participation and their deeper learning. What are these changes and how did they work in the classroom? Were the intended learning outcomes fulfilled? How did the students react to these activities and were they satisfied with the course format and their learning? This project will address these issues as well as further improvements to be applied for increased constructive alignment and student learning in future executions of this course.